Risk Factors Associated with Intraocular Pressure and the Correlation of Central Corneal Thickness to Actual Intraocular Pressure in Myopia Patients - Pandjaitan, Hadwer Wicaksono; Andrini Ariesti (HM Publisher, 2024)
Background: Myopia, a prevalent refractive error, is associated with an increased risk of glaucoma, a leading cause of irreversible blindness. Central corneal thickness (CCT) is a key factor in glaucoma assessment, as thinner corneas can lead to underestimation of intraocular pressure (IOP). This study aimed to investigate the correlation between CCT and actual IOP in myopic patients, considering various risk factors that may influence IOP. Methods: This cross-sectional study included myopic patients aged 20-25 years. Participants underwent comprehensive ophthalmic examinations, including visual acuity assessment, autorefraction, CCT measurement using optical coherence tomography (OCT), and Goldmann applanation tonometry for IOP measurement. IOP values were corrected for CCT. Statistical analysis was performed using ANOVA, Pearson correlation tests, and multivariate regression analysis to identify independent risk factors for elevated IOP. Results: A total of 78 eyes from 78 participants were analyzed. The mean CCT was significantly thinner in moderate myopia compared to mild myopia and emmetropia (p = 0.000). While IOP was lower in moderate myopia, the actual IOP, after CCT correction, was not significantly different among the groups (p = 0.078). A strong positive correlation was found between CCT and IOP (r = 0.737, p = 0.000), and a moderate negative correlation was observed between CCT and actual IOP (r = -0.492, p = 0.000). Multivariate regression analysis identified axial length (p = 0.021) and family history of glaucoma (p = 0.038) as independent risk factors for elevated IOP. Conclusion: This study highlights the importance of CCT assessment in myopic patients, as thinner corneas can mask elevated IOP. Regular eye examinations, including CCT and IOP measurements, are crucial for early detection and management of glaucoma in this high-risk population. Axial length and family history of glaucoma were identified as independent risk factors for elevated IOP, emphasizing the need for comprehensive risk assessment in myopic individuals.